Compressive behavior and failure mechanisms of freestanding and composite 3D graphitic foams - Nakanishi, Kenichi; Aria, Adrianus Indrat; Berwind, Matthew; Weatherup, Robert S.; Eberl, Christoph; Hofmann, Stephan; Fleck, Norman A. (Elsevier, 2018)
Open-cell graphitic foams were fabricated by chemical vapor deposition using nickel templates and their compressive responses were measured over a range of relative densities. The mechanical response required an interpretation in terms of a hierarchical micromechanical model, spanning 3 distinct length scales. The power law scaling of elastic modulus and yield strength versus relative density suggests that the cell walls of the graphitic foam deform by bending. The length scale of the unit cell of the foam is set by the length of the struts comprising the cell wall, and is termed level I. The cell walls comprise hollow triangular tubes, and bending of these strut-like tubes involves axial stretching of the tube walls. This length scale is termed level II. In turn, the tube walls form a wavy stack of graphitic layers, and this waviness induces interlayer shear of the graphitic layers when the tube walls are subjected to axial stretch. The thickness of the tube wall defines the third length scale, termed level III. We show that the addition of a thin, flexible ceramic Al2O3 scaffold stiffens and strengthens the foam, yet preserves the power law scaling. The hierarchical model gives fresh insight into the mechanical properties of foams with cell walls made from emergent 2D layered solids.
Keywords: Cellular solids; Chemical vapor deposition (CVD); Graphene; Micromechanical modeling; Structural hierarchy